2019
DOI: 10.15850/amj.v6n2.1529
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Profile in Health Cadres in Jatinangor, West Java

Abstract: Background: Cardiovascular disease has very high morbidity and mortality, therefore, prevention of this disease becomes a national priority in the health programs. Health cadres, as an agent in community primary prevention, should have a good health condition. This study aimed to describe the cardiovascular risk profile in health cadresin Jatinangor, West Java. Methods: This was a cross-sectional study, conducted in Cilayung Village, Jatinangor, in September 2018. Consecutive sampling was performed on 20 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Pihak Puskesmas juga bisa menindaklanjuti hasil skrining ini, terutama yang teridentifikasi memeliki risiko tinggi untuk mendapatkan pemeriksaan lebih lanjut guna mengantisipasi serta menentukan tindak lanjut yang diperlukan. Temuan risiko DM pada kader ini juga sejalan dengan temuan penelitian yang dilakukan oleh Tiksnadi et al, (2019) Penelitian ini menemukan bahwa sebagian kader memiliki risiko sedang untuk menderita penyakit jantung. Kedua temuan ini menguatkan bahwa penyakit kronik bisa mengenai siapa saja (El Gihart, 2020) termasuk kader kesehatan.…”
Section: Hasil Dan Pembahasanunclassified
“…Pihak Puskesmas juga bisa menindaklanjuti hasil skrining ini, terutama yang teridentifikasi memeliki risiko tinggi untuk mendapatkan pemeriksaan lebih lanjut guna mengantisipasi serta menentukan tindak lanjut yang diperlukan. Temuan risiko DM pada kader ini juga sejalan dengan temuan penelitian yang dilakukan oleh Tiksnadi et al, (2019) Penelitian ini menemukan bahwa sebagian kader memiliki risiko sedang untuk menderita penyakit jantung. Kedua temuan ini menguatkan bahwa penyakit kronik bisa mengenai siapa saja (El Gihart, 2020) termasuk kader kesehatan.…”
Section: Hasil Dan Pembahasanunclassified
“…The Jakarta Cardiovascular Score is based on gender, age, blood pressure, smoking, diabetes mellitus, body mass index and weekly physical activity. 12 Several studies have been conducted in Indonesia to predict coronary heart disease (CHD) incidence using the Jakarta Cardiovascular Score tool. The research conducted on workers at Company X in Jakarta in 2018, showed that 141 people (37.8%) were in the high-risk category, while 118 people (1.6%) were at medium risk for heart and blood vessel disease.…”
Section: Introductionmentioning
confidence: 99%